Depressive Disorders Lead to Increased Complications after Pilon Fracture Surgery. Issue 1 (January 2022) - Tahmid, Syed; Broggi, Matthew S.; Allen, Jerad; Hernandez-Irizarry, Roberto
Category: Trauma; Other Introduction/Purpose: Given the increased survival of the polytrauma patient, the incidence of tibial pilon fractures has increased. Preoperative depression has been linked with worse morbidity and mortality following lower extremity surgery, however its effect on outcomes following tibial pilon fractures has not been studied. This studies purpose was to investigate the relationship between preoperative depression and potential complications following tibial pilon fracture surgery. Methods: This retrospective study utilized the Truven Marketscan claims database to identify patients who underwent outpatient tibial pilon fracture surgery from January 2009 to December 2018 based on Common Procedure Terminology (CPT) codes. The two cohorts entailed patients with and without preoperative depression based on International Classification of Diseases (ICD codes. The associated between preoperative depression and common postoperative complications following tibial pilon fracture was analyzed using chi square testing and multivariate analysis. Results: In total, 4, 795 patients were identified for analysis. In those patients with preoperative depression, the complications associated with the greatest increased odds were infection (OR 1.59), wound complication (OR 1.31), ED visit pain (OR 1.29), hardware complications (OR 1.22), and DVT/PE (OR 1.14). Conclusion: Increased complications and use of healthcare resources have been associated following tibial pilon fracture surgery in persons with a preoperative diagnosis of depression. Acknowledgement of patient's preoperative depression can allow surgeons to tweak treatment protocols before and after surgery. Additional studies should be conducted to investigate the degree of modifiability of depression as a risk factor.